2021
DOI: 10.21037/jtd-21-398
|View full text |Cite
|
Sign up to set email alerts
|

Post-implantation syndrome after frozen elephant trunk is associated with the volume of new-onset aortic thrombus

Abstract: Background: Post-implantation syndrome (PIS) is defined as non-infectious continuous fever and a concomitant rise in inflammatory markers shortly after endovascular aortic repair. PIS occurrence after hybrid procedures, such as the frozen elephant trunk (FET) technique, has not been adequately investigated. The current study aims to define the incidence of PIS after the FET and to identify possible risk factors associated with its occurrence. Methods: The clinical charts of 59 patients undergoing the FET betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Several studies have investigated the incidence of PIS after aortic dissection repair surgery. In a retrospective study of 38 patients who underwent a frozen elephant trunk procedure, the incidence of PIS was 44.7% [ 7 ]. Another study of 74 patients who underwent thoracic endovascular aortic repair (TEVAR) reported an incidence of PIS of 22.97% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the incidence of PIS after aortic dissection repair surgery. In a retrospective study of 38 patients who underwent a frozen elephant trunk procedure, the incidence of PIS was 44.7% [ 7 ]. Another study of 74 patients who underwent thoracic endovascular aortic repair (TEVAR) reported an incidence of PIS of 22.97% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of reported incidence rates can be attributed to differences in patient populations and surgical techniques used in these studies. Ibrahim et al mentioned in their study that PIS occurred in patients who underwent open frozen trunk procedures for type A dissection and ascending aortic aneurysms [ 7 ]. Volevski et al [ 8 ] have reported in their study that PIS occurred following TEVAR.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, its incidence varies widely. In the setting of type B aortic dissections treated with thoracic endovascular aortic repair (TEVAR), PIS incidence has been previously described amounting to 15.8–31.6% [ 11 , 15 ]; in the context of FET, a previous study reported an incidence of 44.7% [ 6 ]. The pathophysiological mechanism of PIS is still largely unknown, while efforts have been made to collect evidence regarding its risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the perioperative care of endovascular-treated patients, post-implantation syndrome is a well-known clinical entity. It was initially described, after endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA) [ 5 ], as a systemic inflammatory response occurring in the early postoperative period and is defined as continuous fever and leukocytosis in the absence of an infection focus; its incidence has been reported amounting to circa 45% in the context of FET [ 6 ]. With the growing application of hybrid stent grafts such as FET for aortic arch lesions and for extensive thoracoabdominal aortic pathologies, PIS issues are becoming increasing relevant in postoperative care.…”
Section: Introductionmentioning
confidence: 99%
“…The exact pathophysiology of PIS and its effects on long-term clinical outcomes remain unclear. Age, medical history, the composition of implanted stent grafts, and the new-onset aortic thrombus volume have been identified as risk factors promoting the occurrence of PIS [6,7,8,10,11,12,13,14,15,16,17,18,19,20,21]. Furthermore, its effect on patient outcomes is a concern because it may lead to prolonged hospitalisation and longer ICU stays [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%